Faster, but not smarter: an experimental analysis of the relationship between mental speed and mental abilities - Schubert, Anna-Lena; Hagemann, Dirk; Frischkorn, Gidon T.; Herpertz, Sabine (Intelligence, 2018)
Individual differences in the speed of information processing may contribute to individual differences in general intelligence by enhancing the efficiency of information processing. So far, this hypothesis is based on correlational data, and thus a causal relationship between mental speed and mental abilities has not yet been established. In the present study, we used transdermal nicotine administration in a double-blind design to increase the speed of information processing and tested whether this increase in information processing speed affected performance in intelligence tests. While nicotine administration decreased both reaction times and P3 latencies in the Sternberg memory scanning task, there was no effect of nicotine on intelligence test performance. These results contradict theories proposing that a greater speed of information processing causes greater intelligence. Instead, they suggest that structural properties of the brain may affect both the speed of information processing and general intelligence and may thus give rise to the well-established association between mental speed and mental abilities.
Gesehen am 27.04.2020